INFRINGEMENT OF ANGIOGENESIS AND SCLEROSIS REGULATION PROCESSES IN HYPERPLASTIC ENDOMETRIUM - N. A. Sheshukova; L. O. Makarov; A. S. Fedotova (Акушерство, гинекология и репродукция)
Pathomorphological and immunohistochemical studies of endometrium were performed. The higher proliferative activity of the VEGF and the higher production of transformation growth factor β1 (TGFβ1), fibronectin and liziloxydaza in patiens with atypical hyperplasia of endometrium and chronic endometritis testifies the presence of cellular hypoxia, disturbance of intercellular and extracellular interaction and can be considered as the negative prognostic factor.